Selective photoelectrochemical oxidation of glycerol to high value-added dihydroxyacetone - Liu, Dong (2019)
It is highly profitable to transform glycerol – the main by-product from biodiesel production to high value-added chemicals. In this work, we develop a photoelectrochemical system based on nanoporous BiVO4 for selective oxidation of glycerol to 1,3-dihydroxyacetone – one of the most valuable derivatives of glycerol. Under AM 1.5G front illumination (100 mW cm−2) in an acidic medium (pH = 2) without adscititious oxidant, the nanoporous BiVO4 photoanode achieves a glycerol oxidation photocurrent density of 3.7 mA cm−2 at a potential of 1.2 V versus RHE with 51% 1,3-dihydroxyacetone selectivity, equivalent to a production rate of 200 mmol of 1,3-dihydroxyacetone per m2 of illumination area in one hour.